Geoprocessamento aplicado à cartografia histórica do município de Santo Antônio do Tauá – PA - SILVA FILHO, Gilberto da Cruz e (2020)
The present work used geoprocessing tools for the verification of old maps (Historical Cartography), analyzing the changes that occurred in the land pattern in Santo Antônio do Tauá-PA, taking into consideration the distribution of lots in the Santa Rosa Colony area. which was installed in 1898 and emancipated in 1902. The dynamics of this colony over time help to understand the patterns of ordering in the municipality from the late nineteenth century. For this, historic plants of the Santa Rosa colony were used, being selected two plants of discrimination of agricultural lots, one from 1898 and the other from 1981, where both were digitalized, geo-referenced redrawn through control points angles and azimuths in the Autocad software. With the help of field control points, IBGE cartographic bases, Open Street Map, SICAR base and fused LANDSAT 8 satellite image. The other plants of the Iracema and Granja América Nucleus were georeferenced and then vectorized. Geometric distortions arising from the scanning and photography methodologies of the colonies were minimized with the aid of specific software, as well as the conversion of scale differences and projections. As a result, multitemporal crop maps were generated (1898, 1981 and 2018), making it possible to compare the land pattern, identifying permanencies and changes such as the predominance of small property and, more punctually, a concentration of land. We also analyzed the relationship between occupation and environmental variables (drainage, relief and soils) and current land use vectors, with emphasis on urbanization. The results of the work underscored the potential of geoprocessing for historical analysis, and more particularly for historical geography.